LANGUAGE FUNCTIONS AND EXPRESSIONS IN HANDLING COMPLAINT: AN ANALYSIS OF GRAMMAR USED BY RECEPTIONISTS AT BALI MANDIRA BEACH RESORT AND SPA. - Hanamika Rusli; Made Dharma Susena Suyasa; Made Aryawan Adijaya (Lingua Scientia, 2025)
Language functions and expressions are important in handling various complaints in hospitality context. This study aimed to analyse the types of guest complaints, the language functions and expressions used, and the grammatical accuracy demonstrated by front office receptionists at Bali Mandira Beach Resort and Spa. This study employed a descriptive qualitative approach. The data were collected through direct observation and semi-structured interviews involving four receptionists experienced in handling guest complaints. The analysis in this study was guided by Norwell’s theory (2005) in classifying the types of complaints. The language functions were analyse based on Jakobson’s theory (1960), and Wirtz’s theory (2018) regarding service recovery expressions was also employed. In analysing grammatical elements, Celce-Murcia and Larsen-Freeman’s theory (1999) was employed. The findings reveal that four types of complaints were used by the guests, namely service-related, mechanical, attitude-related, and unusual complaints. In handling those complaints, the receptionists predominantly used emotive, referential, and conative language functions, realized through apologies, expressions of empathy, clarification, solution offering, and compensation. This study also reveals that although communication was generally effective, several grammatical errors were used by the receptionists, particularly in the usage of verb in tenses and subject–verb agreement. These findings suggest that language functions and expressions as well as grammatical knowledge play an important role in maintaining professionalism in hospitality service interactions and should be mastered.